Miss Fox's Class Goes Green - Spinelli, Eileen; Kennedy, Anne, 1955- (Morton Grove, Ill. : Albert Whitman, 2009)
The students in Miss Fox's class lead their school in making choices to help keep the planet healthy, such as turning off lights when leaving a room, taking shorter showers, and using cloth bags instead of plastic ones.
Accelerated Reader AR